The asset-and-liability view and the income concepts in Japan / Hiromasa Okada - Okada, Hiromasa (Accounting Research Institute (ARI) & Faculty of Accountancy, 2008)
This paper clarifies the fundamental income computational structure under the Asset-and-Liability view. According to this income view, income is the increase/decrease in the net asset of an enterprise and key concepts are asset and liability. Thus, in the fundamental income computational structure, income is calculated in the balance sheet with the causes of income being explained in the income statement. However, the income statement does not necessarily have to explain all causes of income. In the clarification of the fundamental structure, this paper examines income concepts defined in the memorandum of the ASBJ (Accounting Standards Board of Japan) where comprehensive income and net income are defined. Comprehensive income is to be based on the Asset-and-Liability view, net income on the Revenue-and-Expense view. These two income concepts may lead to duality of periodical income allocation in Japan. This paper considers the reason for co-existence of two different types of income in terms of the fundamental income computational structure of the Asset-and-Liability view.